Advancing access to substance use prevention for foster youth through digital innovation: an open trial of fostrspace with court appointed special advocate programs - Marina Tolou-Shams; Johanna B. Folk; Margareth V. Del Cid; Jannet Lara Salas; Alison Czopp; Juan Carlos Gonzalez; Tylia Lundberg; Erin Michelle Turner Kerrison; Martha Shumway; Ann Wrixon; Robert Salgado; Jill Duerr Berrick (BMC Health Services Research)
Abstract Background Adolescents in foster care report high rates of mental health needs, yet intervention access remains limited. Substance use commonly co-occurs with mental health symptoms, but availability of substance use services for foster youth is even more scant than mental health services. Technology has advanced access to behavioral health care across the lifespan, but only for certain sectors of the population. Little research focuses on leveraging technology to advance access for foster youth. We report open trial findings, as a precursor to launching a large-scale implementation science trial, on how a U.S. nationwide serving support system for foster youth, Court Appointed Special Advocates (CASA), might be leveraged to expand access to substance use prevention resources via the FostrSpace app. FostrSpace provides asynchronous resources and synchronous navigator, peer support, and direct clinical intervention. A concurrent 6-session ECHO® substance use prevention telementoring curriculum was co-developed as a FostrSpace implementation strategy with a 6-member CASA Advisory Board. Methods Seven youth-CASA dyads enrolled in the open trial. We used a mixed-methods design (quantitative assessment and qualitative exit interviews) to assess feasibility and acceptability of ECHO® sessions (CASA-only) and the usability of the FostrSpace app (youth-only). Results Six of seven of the youth accessed the app at least once, but a majority reported the app log-in process was burdensome and unappealing, thereby limiting them from frequently using the app. All youth rated the app features, design and content as appealing, helpful and relevant. ECHO® -FostrSpace session attendance was high (most attended 5 or more sessions) and CASAs found the content highly engaging and useful, especially regarding CASA-youth substance use communication skills. Conclusions Technological barriers, such as log-in burden, can prevent youth in need from accessing relevant services and must be regularly assessed and resolved. Substance use education and skills-building for CASAs is novel and a viable implementation strategy to increase foster youth access to digital behavioral health services innovations. Substance use prevention content should be integrated within discussions on youth mental health and trauma to be most engaging and relevant. Findings are informing the subsequent hybrid implementation-effectiveness trial design of FostrSpace with 400 youth-CASA dyads across 10 CASA programs in California. Trial registration Retrospectively registered.